Литье в кокиль - Бураков С. Л. Савелий Леонидович; Вейник А. И. Альберт Иозефович; Дубинин Н. П. Николай Петрович; Петриченко А. М.; Рывкис Я. М.; Серебро В. С. (Москва, Машиностроение, 1980)
Авт. указаны на обороте тит. л.